Perancangan dan Pengembangan Web Profile SMP Negeri 1 Teriak Kabupaten Bengkayang - p, noviyanti; Gudiato, Candra; Kusnanto, Kusnanto (STMIK Royal, 2024)
The problem discovered during interviews conducted between the principal, deputy principal, and lecturers at the Shanti Bhuana Institute was that when the SMPN 1 Teriak school was searched on the internet, no complete identity regarding the school was found, for example history, vision and mission, school excellence and school activities. both academic and non-academic. Based on the problem identification carried out at SMPN 1 Teriak school through interviews and observation methods, the principal hopes that there will be a website that the school can use as a medium for information and promotion. The solution offered by the Shanti Bhuana Institute lecturer was to develop a web profile for the SMPN 1 Teriak school, Bengkayang Regency using WordPress. The school's web profile was designed and developed by lecturers at the Shanti Bhuana Institute. The design and development of the web profile has been socialized and simulated to the school. This web profile can be used by schools to provide interesting content in the form of news about school activities, videos of school activities, and photo galleries of school activities. There are many things that the school can share through its web profile so that SMPN 1 Teriak, Bengkayang Regency can become better known to the public and can become a developing school with advantages that can be enjoyed by both teachers and pupils. Keywords: Community Service; Web Profile; WordPress; SMPN 1 Teriak; Bengkayang Regency Abstrak: Permasalahan yang ditemukan selama wawancara yang dilakukan antara kepala sekolah, wakil kepala sekolah, bersama dosen Institut Shanti Bhuana adalah ketika sekolah SMPN 1 Teriak dicari di internet tidak ditemukan identitas yang lengkap terkait sekolah, misalnya seperti sejarah, visi misi, keunggulan sekolah, dan kegiatan sekolah baik akademik maupun non akademik. Berdasarkan identifikasi masalah yang dilakukan pada sekolah SMPN 1 Teriak melalui metode wawancara dan observasi, kepala sekolah mengharapkan adanya suatu website yang dapat digunakan sekolah sebagai media informasi dan promosi. Solusi yang ditawarkan oleh dosen Institut Shanti Bhuana adalah memgembangkan web profile untuk sekolah SMPN 1 Teriak Kabupaten Bengkayang menggunakan Wordpress. Web profile sekolah dirancang dan dikembangkan oleh pihak dosen Institut Shanti Bhuana. Perancangan dan pengembangan web profile tersebut telah disosialisasikan dan disimulasikan kepada pihak sekolah. Web profile ini dapat dimanfaatkan oleh pihak sekolah untuk memberikan konten yang menarik berupa berita kegiatan sekolah, video kegiatan sekolah, dan galeri foto kegiatan sekolah. Banyak hal yang dapat pihak sekolah share melalui web profile sehingga SMPN 1 Teriak Kabupaten Bengkayang dapat semakin dikenal oleh masyarakat dan dapat menjadi sekolah yang berkembang dengan keunggulan yang dapat dinikmati oleh guru maupun siswa/siswa.Kata kunci: Pengabdian Kepada Masyarakat; Web Profile; Wordpress; SMPN 1 Teriak; Kabupaten Bengkayang.